"Questioning the Relationship. Between Children's Spirituality and Traditions". Report on the 16th International Conference on Children's Spirituality. Issue 1 (2nd January 2019) - Stockinger, Helena
ABSTRACT: The 16th International Conference on Children`s Spirituality „Questioning the Relationship. Between Children`s Spirituality and Traditions" took place from the 24th to th 27th of July 2018 at the Laval University in Quebec, Canada. The report gives a review of the conference and summarizes some findings.